Hubungan Self Efficacy Dengan Self Regulated Learning Pada Mahasiswa Bk Uin Mahmud Yunus Batusangkar - Rismawati Rismawati; Rina Yulitri; Rahmad Hidayat; Dasril Dasril (Empowerment Counseling Journal, 2025)
Self-regulated learning (SRL) is an important skill that students, especially Guidance and Counseling students, must possess because it relates to the ability to manage their learning process independently. However, in practice, students are still found to be unable to optimize this skill. This study aims to determine the relationship between self-efficacy and self-regulated learning in Guidance and Counseling students of UIN Mahmud Yunus Batusangkar, class of 2022. Self-efficacy in this study is examined through three aspects: level, generality, and strength, while self-regulated learning through aspects of metacognition, motivation, and behavior. The research method used is quantitative with a correlational type. The population in this study were Guidance and Counseling students of UIN Mahmud Yunus Batusangkar, class of 2022, with total sampling. The research instrument was a Likert Scale compiled based on the indicators of the two variables. Data analysis was carried out using product-moment correlation through the SPSS version 21 program. The results showed that, in general, the level of self-ability and self-regulated learning of guidance and counseling students was in the high category. The correlation coefficient value obtained was r = 0.686 with a significance level of 0.000 (p < 0.05). This indicates a significant positive relationship between self-efficacy and self-regulated learning. Thus, the higher a student's self-efficacy, the higher their ability to manage the learning process independently. The findings of this study strengthen previous literature and contribute to the development of learning strategies and guidance services that emphasize increasing students' self-confidence and learning regulation skills.